Pengaruh Pemberian Jus Wortel (Daucus carota, Linn) Terhadap Kadar Glukosa Darah Mencit Putih Betina - Surya Dharma; Hendra Saputra; Netty Suharti (Jurnal Farmasi Higea, 2011)
Research on the effect of carrot juice (Daucus carota, Linn) on blood glucose levels of female white mice have been  done. These experiments use advantage glucose meter (Roche) to measure the glucose blood level  with the enzymatic method. The treatment carried out for 21 days with observation time at day 7, 14 and 21. carrot juice given Doses is 0.52; 1.04, and 2.08 g/20g bw. The results showed that administration of carrot juice at all dose groups can lower blood glucose levels of mice was significantly (P, 0.05) After giving 3 mg/20 g bw alloxan and glucose 195 mg/20 g bw.